The Islamic Education According to Muhammad Natsir - Ukhrowi, Muhammad Zaim; Muhibbin, Much. Ihsaanul; Ibrahim, Rustam (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Islamic education plays a crucial role in improving the quality of human resources. Ideally, Islamic education functions to prepare high-quality human resources, focusing on both mastery of knowledge and the practice of religious teachings. Therefore, Islamic education must be integral, harmonious, and universal so that humans can fulfill their duties as khalifah (steward) and servants of Allah. This educational concept was advocated by Muhammad Natsir during the late colonial period in the Netherlands. One of the perspectives Natsir used to integrate education was by establishing integrative Islamic educational institutions (Pendis), which combined religious education with general education, preventing a divide between the two. At that time, religious education was heavily influenced by traditionalist Islam, while colonial government education and modernist Muslims emphasized worldly knowledge and skills. The goal of Islamic education as envisioned by Mohammad Natsir was to shape individuals who are faithful, pious, ethical, advanced, and independent, possessing high spiritual resilience and the ability to adapt to the dynamics of societal development. Moreover, the purpose of human life is to attain happiness both in this world and the hereafter, which can only be fully achieved by both. Islamic education is inseparable from human life.